Prolonged signaling of backbone-modified glucagon‐like peptide‐ 1 analogues with diverse receptor trafficking - Brian P. Cary; Marlies V. Hager; Zamara Mariam; Rylie K. Morris; Matthew J. Belousoff; Giuseppe Deganutti; Patrick M. Sexton; Denise Wootten; Samuel H. Gellman (Proceedings of the National Academy of Sciences, 2025)
Signal duration and subcellular location are emerging as important facets of G protein–coupled receptor (GPCR) function. The glucagon-like peptide-1 receptor (GLP-1R), a clinically relevant class B1 GPCR, stimulates production of the second messenger cyclic adenosine monophosphate (cAMP) upon activation by the native hormone, GLP-1. cAMP production continues after the hormone–receptor complex has been internalized via endocytosis. Here, we report GLP-1 analogues that induce prolonged signaling relative to GLP-1. A single β-amino acid substitution at position 18, with the residue derived from ( S , S )- trans -2-aminocyclopentanecarboxylic acid (ACPC), enhances signaling duration with retention of receptor endocytosis. Pairing ACPC at position 18 with a second substitution, α-aminoisobutyric acid (Aib) at position 16, abrogates endocytosis, but prolonged signaling is maintained. Prolonged signaling is sensitive to the structure of the β residue at position 18. Cryoelectron microscopy structures of two GLP-1 analogues bound to the GLP-1R:Gs complex suggest substantial alterations to bound peptide structure and dynamics compared to the GLP-1:GLP-1R:Gs complex. These structural findings strengthen an emerging view that agonist dynamics in the receptor-bound state influence signaling profiles. Our results advance understanding of the structural underpinnings of receptor activation and introduce tools for exploring the impact of spatiotemporal signaling profiles following GLP-1R activation.